The Dancing Eyes of the Director: Choreographers, Dance Cultures, and Film Genres in British Music Video 1979–2016. Issue 1 (July 2017) - Caston, Emily
Abstract : This article looks at the work of choreographers in British music video from Arlene Phillips (founder of Hot Gossip), to FKA Twigs and Wayne McGregor. The first section presents an overview of the development of genres of dance and choreography in music videos from the late 1970s to the present day, covering genres such as the loosely-choreographed pop act video, to the formal, tightly-choreographed routines of videos drawing on the Hollywood musical tradition, to the street dance video ushered in following Malcolm McLaren's breakthrough 'Buffalo Gals' video (1983). The article argues that British music videos should not be negatively compared to their bigger budget US counterparts but should instead be appreciated on their own merits – and those merits include the greater creative exchange with ballet and contemporary dance, and the use of techniques from experimental film and narrative film; and it argues that these features make dance in British music videos an exciting and critically acclaimed cultural form today. The author draws attention to the importance of 'social realism' within British choreographed music videos, and points out that the recent work of Matthew Bourne and FKA Twigs overrides the traditional distinction between 'dance film' and commercial music dance film. This article was published open access under a CC BY licensehttps://creativecommons.org/licenses/by/4.0/